A Kualitas kulit nanas (Ananas comosus (L) Merr) hasil perendaman alkali dan pengaruh pemberiannya terhadap performa ayam broiler - Weveri Dilahari; Erica B Laconi; Purwiyatni Hariyadi; Rukmiasih (Politeknik Negeri Jember, 2022)
The purpose of this study was to examine the effect of alkaline soaking time on the crude fiber and protein fractions of pineapple peel. The research consisted of two stages, the first stage was immersion of pineapple peel with husk ash water filtration concentration (FAAS) and different soaking times, and the second stage was about giving basic pineapple peel flour (TNKB) with different percentages in the ration. The first stage used a factorial completely randomized design consisting of FAAS concentration factors of 20%, 30%, and 40%, and immersion time factors of 0, 24, 48, and 72 hours. The second stage used a completely randomized design (CRD) with 0%, 5%, 10%, and 15% TNKB treatments in the ration. The best reduction in fiber and crude protein fractions from alkaline soaking preparations will be given to broiler chicken feed rations. The result of immersion of 30% concentration with soaking time for 72 hours showed the best decrease for the fiber fraction. So that this processed pineapple skin flour can be given to broiler chicken feed rations. The results of the study concluded that the use of alkaline acidification of pineapple peel in rations could be used up to a level of 15% without affecting the performance of broiler chickens.